An Anthropometric History of Early-Modern France - John Komlos; Michel Hau; Nicolas Bourginat (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2003)
The height of the French male population of the Ancien Régime is estimated, on the basis of military records, to have been about 162 cm in the 17th century. This extremely short stature implies that, “the crisis of the 17th century” had an immense impact on the human organism itself. The improvement in climatic conditions at the turn of the 18th century had an ameliorating effect on the human organism, increasing in size by nearly 4 cms within a span of 12 years. Improved weather had a beneficial impact on agricultural conditions as well as a direct effect on biological processes. The physical stature of men increased until the birth cohorts of the 1740s, to decline thereafter, in keeping with the European pattern, although the decline of the second half of the 18th century was not more severe than elsewhere in Europe. France was not suffering from a prolonged period of malnutrition of unusual severity, and the threat of a Malthusian crisis was mild compared to 17th-century conditions. Hence, the anthropometric evidence supports the notion that the French economic malaise was not a fundamental cause of the political turmoil. To be sure, there were very large social differences in the biological standard of living, which clearly fuelled the fires of revolution. The height of the French upper classes was 7 cm above average, but, that, too, was standard for contemporary Europe.
urn:nbn:de:bvb:19-epub-54-5
Keywords: I12; N33; 330; Anthropometric History; Early Modern France; biological standard of living